PENGARUH PROMOSI KESEHATAN TENTANG PENCEGAHAN HIV/AIDS TERHADAP PENGETAHUAN, SIKAP, DAN PERILAKU POPULASI KUNCI - Gusni Rahma; Yulia Yulia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: AHIV/AIDS remains a major public health problem, particularly among key populations with a higher risk of transmission due to behavioral, social, and structural factors. Health promotion is an important strategy to improve knowledge, develop positive attitudes, and encourage preventive behavior. This study aimed to analyze the effect of health promotion on HIV/AIDS prevention toward knowledge, attitudes, and preventive behavior among key populations in Padang City. This study employed a quantitative pre-experimental design with a one-group pre-test and post-test approach. A total of 60 respondents were selected using purposive sampling. The intervention was conducted for one month through participatory health education, small group discussions, educational media, simulation, and digital follow-up. Data were collected using questionnaires and analyzed using univariate and bivariate analyses. The results showed an increase in good knowledge from 38.3% to 75.0% (p=0.001), positive attitudes from 43.3% to 73.3% (p=0.003), and good preventive behavior from 40.0% to 70.0% (p=0.005). Health promotion was effective in improving knowledge, attitudes, and HIV/AIDS preventive behavior among key populations in Padang City.Keywords: HIV/AIDS, health promotion, key populations, knowledge, preventive behavior.